The Digital Scalpel: Does AI Truly Improve Surgical Outcomes? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into surgical medicine represents one of the most transformative shifts in modern healthcare. Moving beyond the...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning